Implementasi Model Problem-Based Instruction berbantuan Artificial Intelligence pada mata Pelajaran Dasar-Dasar Program Teknik Ketenagalistrikan - Putra, Febi Siska; Usmeldi, Usmeldi (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2024)
This study aims to determine the improvement of student learning outcomes and the percentage of student skills after implementing the Problem-Based Instruction learning model assisted by Artificial Intelligence in the Basic Electricity Engineering Program subject. This study used experimental methods with the type of pre-experimental type one-group Pretest-Posttest Design. The research subjects were students of class X TITL SMK Adi Karya in the academic year 2023/2024 consisting of 15 students. In this study, the type of experimental method used a pretest, which was carried out before being given treatment. Furthermore, after being given treatment, a posttest will be carried out. The implementation of the Problem-Based Instruction learning model assisted by Artificial Intelligence is very effective in the X TITL class at SMK Adi Karya, this can be seen from the increase in the average pretest score and the average posttest score and by calculating student skills, the student skill category is obtained as very skilled. Then Cohen's effect size calculation formula shows a large category. Using the Problem-Based Instruction learning model assisted by Artificial Intelligence can increase understanding of learning materials and the active role of students so that it affects their learning outcomes.